E waṃ Lcog sgar gyi bcaʼ yig bslab btus Sdom gsum lam gyi sñiṅ po gsal byed baiḍūrya dag paʼi me loṅ : the rules and ordinances of the Central Tibetan Monastery of Rdo-rje-brag - Padma-phrin-las, Rdo-rje-brag Rig-ʼdziṅ II, 1640?-1718 (Gar źa Śa śin Śes rig Dpe mdzod khaṅ ;, 1979)
Instructions on the Buddhist formula, with the preliminary practices of the rules and ordinances according to the Nyingmapa tradition.